African Studies and the Question of Diasporas - Bewaji, John Ayotunde (Tunde) Isola; Institute of African Studies (University of Bayreuth African Studies Working Papers, 2021)
The concept Diaspora applied to Africa is a misnomer of sorts, bearing in mind that Africa was the original home of the oldest human beings. Science has discussed how the earlier waves of emigrant Africans (humans originally domiciled in Africa) have adapted to their environment, becoming various shades as melanin presence dictated. Later groups are in India, Tonga, New Zealand, Australia, the Americas: black skinned, flat nose, but with various forms of stretchered out hair. These earlier groups are not called, technically, Diaspora. Only recent migrants to the West, Europe, Asia Minor, Asia and the Americas are called Diaspora: they migrated voluntarily for various reasons or they were forced out of Africa as captives. Part of the challenges that African Studies instigate are fraught because of (a) the participation of continental Africans in slavery wars in Eastern, Central Africa, Northern and Central Africa; (b) the Middle Passage of the Atlantic and the Sahara/Pacific; (c) the empty baggage syndrome and epistemicide and, (d) the Willie Lunch Syndrome of Divide and Conquer exemplified in Obama phenomenon. African studies writ large must then encompass (a) Repairing the Breach; (b) Recovering the Heritage - Calypso, Blues and Jazz, Reggae, Rastafari, Sports; (c) Restoring Indigenous Knowledge Systems by erasing epistemicide and (d) Restoring the African humanity. These efforts must be multi/inter disciplinary and encompass all domains of human intellectual theory and practice. Recovering the human intellectual traditions and knowledge systems of continental and Diasporas would be a treasure trove of ideas to solve many of the challenges faced by humanity today; this will require transcending what Claude Ake has dubbed “Social Science as Imperialism”. In this essay, I attempt to sketch what would constitute a more appropriate, historiographically accurate and globally judicious understanding of African Studies that is holistic. My goal is to sketch an African Studies that is not segmented on the basis of the agendas of exogenous forces bent on decimating global African peoples, by playing diverse groups against each other, but one which recognizes the continuity of human heritage as primarily African heritage writ large, and one which recognizes that the African Diasporas, recent and classical, are all continuous with Africa feeding and renewing the world with humanity by virtue of being the original home of humanity. This calls for so many different approaches, but primary being the complete overhaul of the current curricula used to programme the minds of humanity, especially those emanating from European climes, to persist in negro-gaze: the objectification and exoticization of Africa and peoples of Africa globally, thereby derogating their humanities and agencies.
Keywords: Diaspora; Migration; Philosophy; Literature; Cluster of Excellence Africa Multiple; African Studies; indigenous knowledge systems; humanity; Africa